A Convenient and Environmentally Benign Method of Reducing Aryl Ketones or Aldehydes by Zinc Powder in an Aqueous Alkaline Solution - 张超智 杨辉 吴德林 陆国元 (Chinese journal of chemistry, 2007)
A convenient and environmentally benign method for reducing the carbonyl group in hydroxy- and amino- 9,10-anthracenediones, ortho （or para） acyl phenols and acyl anilines to a methylene group by zinc powder in an aqueous sodium hydroxide solution was reported. Based on theoretical calculations using the density functional theory （DFT）, the mechanism of these reduction reactions was postulated. This mechanism can be applied to help predicting the reduced products of aryl ketones （or aldehydes） in an alkaline solution.